The 1999 general elections in Malaysia: towards a stable democracy? - Abdul Rashid Moten (Universiti Kebangsaan Malaysia, 2001)
The 1999 general elections in Malaysia have brought about a significant change in the distribution of partsanship in the electorate. It redefined the relationships between social groups and party support. It witnessed an assertive role palyed by various non-governmental organizations and other civil and political forces in the society. The contesting parties debated serious issues at different levels and have accepted the results with grace. The results showed an encouraging movement towards a two-coalition ‘turnover’ system that allows for deepening democracy in Malaysia.